g(n)=25-49(n-1)

Simple and best practice solution for g(n)=25-49(n-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for g(n)=25-49(n-1) equation:


Simplifying
g(n) = 25 + -49(n + -1)

Multiply g * n
gn = 25 + -49(n + -1)

Reorder the terms:
gn = 25 + -49(-1 + n)
gn = 25 + (-1 * -49 + n * -49)
gn = 25 + (49 + -49n)

Combine like terms: 25 + 49 = 74
gn = 74 + -49n

Solving
gn = 74 + -49n

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Divide each side by 'n'.
g = 74n-1 + -49

Simplifying
g = 74n-1 + -49

Reorder the terms:
g = -49 + 74n-1

See similar equations:

| k/3=-16 | | ((2x^3-2/7))^3 | | -32=-17+x | | 99=9y | | -0.6u-9=-5 | | 2(3z-1)-2(4-2Z)=8 | | 13x-7=12x-12+x+5 | | -3/2y=22 | | 75-9n= | | p/14=1 | | -20=k-19 | | 10x-16=8x+7 | | -54=9h | | 4b+2=9b-23 | | 0.28y+8=11 | | 3(6x-5)=18x+15x | | b/17=-13 | | 4(x-30)+5x=-48 | | x+(1+x)+(2+x)=228 | | 5r-4r=16 | | -8(9h-5)=-17 | | -12+4n=4 | | -11+b=-3 | | 19a-12-4a=(-57) | | (Y6/Y3)4 | | k/18=-4 | | 393=17n+2 | | 13=11-y | | m/15=16 | | -6x-10=-16 | | -5d-24=4(1d+6)-1d | | 6x+21=6x+24-3 |

Equations solver categories